The effect of home delivery and click-and-collect services on online grocery order fulfilment: a cross-case analysis in the Czech Republic - Tran, Thu Thuy (2020)
Grocery was one of a limited few retail subsectors that experienced sustained volume and value growth in 2020 (McKinsey, 2021). In Eastern European, the Czech Republic’s e-commerce sector is regarded to be more developed than that of its counterparts in the region. This study contributes to the academia’s understanding of the grocery retail industry in the Czech Republic by investigates the online grocery fulfilment, including home delivery and click-and-collect services in the country based on three elements: last-mile delivery, warehousing and order preparation, using primary data from semi-structured in interviews with experts and professionals in grocery retailing in the Czech Republic and secondary data from desk research. The research shows that home delivery is still far more preferred than click-and-collect for online food shopping in the Czech Republic. Moreover, a centralised distribution system with different level of automation is mostly used by grocery wholesalers in the Czech Republic. Discrete (single-order) picking remained the only picking method for online grocery orders among two case wholesalers. This paper is organised into five main chapters. In the first chapter, introduction is given on the grocery retail industry and the market structure in the Czech Republic. In the second chapter, a literature review on omni-channel retailing, click-and-collect, home delivery is conducted. Based on the conceptual frameworks and literature, the author proposed a research framework to study about the online grocery order fulfilment in the Czech Republic, consisting of three elements. In the third chapter, the research methodology is discussed, particularly for the collection of primary and secondary data, as well as the analysis of these data. Research findings is presented separately for grocery retailers and grocery wholesalers in Chapter 4. In the last Chapter, the main results are discussed and the managerial implications and the research limitations are explored.